Strengthening Self-Management among Older Adults at Jubilee Home Penang, Malaysia: An Organizational Behavior Perspective - Alice Erni Husein; Daniel Cassa Agustinus (Jurnal Locus Penelitian dan Pengabdian, 2026)
This community service article reports a behavior-based intervention aimed at strengthening self-management among older adults residing at Jubilee Home Penang, Malaysia. Drawing on organizational behavior and self-regulation theory, the program responds to the growing need for psychosocial empowerment of older adults in institutional care settings. The intervention was designed using a participatory approach and implemented through four stages: initial behavioral assessment, structured educational sessions, guided self-reflection and practice, and qualitative evaluation. Data were collected through systematic observation, facilitator field notes, and participant feedback. The findings demonstrate meaningful improvements in self-awareness, emotional regulation, daily activity structuring, and perceived personal control among participants. This article offers novelty by extending organizational behavior concepts traditionally applied in workplace contexts into community service for older adults, positioning them as active agents of behavioral regulation. The program contributes a theoretically grounded and replicable model of community service that emphasizes behavioral agency and self-efficacy in later life